Performance analysis of interference coordination techniques in heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Mohd. Ramli, Huda Adibah (Maxwell Scientific Organization, 2014)
Deploying femtocell in heterogeneous network (HetNets) are promising because of improved coverage as well as system capacity. The challenge for inter-cell and intra-cell interference has taken seriously by the industry. However, some distinctive characteristics presents key problem to mitigate the interference. The random deployment of femtocell (HeNodeB) and other small cell in HetNet becomes a key considerations issue because of interference which lead the performance degradation. The interference occurs between HeNodeB-to-macro cell and HeNodeB-to-HeNodeB in the case of uplink/downlink with the user equipments. Consequently, researchers have proposed some techniques to take over the interference in HetNet which need to be investigate, identify, quantify along with solution. Therefore, the aim of this study to evaluate the performance of potential interference alleviation schemes/techniques in Orthogonal Frequency Division Multiple Access (OFDMA) considering HetNets uplink/downlink scenario.